Ayurvedic dentistry: An unsung past to a bright future - Anzil KS Ali; Rajani ER; Shuhaib A Rahman; Kiran M; Krishnaveni L; Licy maria P (Journal of Orofacial Research, 2020)
Ayurvedic material has been proven to be safe and effective through ages, and numerous Indian medicinal plants are being used in articulating beneficial measures. Dental fraternity has witnessed the footprints of these herbal products in the form of toothpastes, mouthwashes, gumpaints, root canal irrigants etc. Ayurveda also recommends the daily use of therapeutic procedures and preventive measures such as dant dhavani, jivha lekhana and gandoosha or oil pulling. Herbs exhibit unique therapeutic properties like antibacterial, antiinflammatory, astringents, anticariogenic and as tooth whiteners. Various studies have been conducted in the past to evaluate the efficacy of these herbs in dentistry and have shown favorable results. The present review article focuses on the benefits of the common medicinal herbs used in dentistry.